A facile synthesis of layered double hydroxide based core@shell hybrid materials. (11th March 2020) - Lyu, Meng; Chen, Chunping; Buffet, Jean-Charles; O'Hare, Dermot
Abstract : A simple and scalable co-precipitation method to obtain zeolite Z13X@Mg2 Al–CO3 -LDH and Mg-MOF-74@Mg2 Al–CO3 -LDH has been reported. Abstract : A zeolite@layered double hydroxide (LDH) core–shell hybrid (Z13X@Mg2 Al–CO3 LDH) and a metal organic framework (MOF) MOF@LDH core–shell hybrid (Mg-MOF-74@Mg2 Al–CO3 LDH) have been synthesised using a simple, scalable co-precipitation method. The effects of the synthesis parameters on the phase purity, crystallinity, morphology, composition, thermal stability, Brunauer–Emmett–Teller (BET) specific surface area and porosity of the core–shell hybrid have been investigated. Rapid metal nitrate addition was found to facilitate the growth of LDH shells with good crystallinity and thickness (250 nm). Ageing times of 0.5 and 16 hours were found to promote the formation of core@shell materials with high BET specific surface areas of 517 and 514 m 2 g −1, respectively.